Comparative study on government subsidy models for competitive drug supply chains under centralized procurement policy - Wen, Yan; Wei, Yan; Liu, Lu (Frontiers in Public Health, 2025)
As the generic drug market tends to be saturated, the structural transformation of generic drug companies is imminent, while the high investment and high-risk attributes of innovative drug research and development aggravate the transformation difficulties. Against the backdrop of drug centralized procurement policy, considering the effect of health insurance reimbursement and market competition ferocity, this study constructs a differential game model of a secondary drug supply chain comprising two competing drug companies and a single healthcare institution. In addition, this study comparatively analyzes the optimal equilibrium strategies and supply chain profit levels of drug research and development investment and healthcare service efforts under four government subsidy modes, further discussing them along with arithmetic examples. It is found that the government's subsidy behavior markedly influenced drug companies' investment in drug research and development and healthcare institution' service cost investment. Besides, different incentives for supply chain members' decision-making and profits were noted in different markets with different competition intensities. In the low-intensity competition market, the government's subsidies to innovative drug companies generate much higher social welfare than other modes. In the high-intensity competition market, the government subsidized healthcare institution can minimize the mutually exclusive effects of subsidies on the development of innovative and generic drug companies, and eventually drive the reform and development of the entire drug industry.